The effect of shift work on burnout and occupational fatigue among clinical faculty members during the COVID-19 pandemic - Gilavand, Abdolreza (Frontiers in Public Health, 2022)
Introduction: Considering that shift work of clinical faculty members in COVID-19 pandemic may cause burnout and occupational fatigue, and as a result, may reduce the quality of student education and disrupt the treatment of patients, so this study was conducted to evaluate this case. Materials and methods: The statistical population of this cross-sectional research included all clinical faculty members of Ahvaz Jundishapur University of Medical Sciences in southwestern Iran, who experienced a shift work system (Night shift from 8 pm to 8 am) during COVID-19 pandemic, and finally, 71 of them participated in it. Sampling method was also available. Two inventories were used to collect data, namely Maslach Burnout Inventory (MBI-HSS (MP)) and Swedish Occupational Fatigue Inventory (SOFI-20). Results: The self-reported burnout of faculty members was high (Mean ± SD= 98.18±17.18), which was graded into the range of emotional exhaustion (38.01±10.2), range of personal accomplishment, (33.75±6.75) and the range of depersonalization (26.42±3.5) respectively. Perceived occupational fatigue of faculty members was also high (M±SD=82.25±34.79), which included the dimensions of lack of motivation (18.69±8.65), drowsiness (17.43±8.7), lack of energy (16.33±7.67), physical discomfort (15.65±8.62), and physical stress (13.51±6.9), respectively. In terms of demographic characteristics, occupational fatigue was significant more common among women. Discussion and conclusion: The self-reported burnout and occupational fatigue of clinical faculty members due to shift work were reported to be high in this study. Although our knowledge of burnout has advanced in recent years, many gaps in our knowledge still remain. In order for clinical faculty members to properly fulfill their mission to treat patients, educate students, and promote public health, it is necessary to provide all the necessary conditions for their effective activity. Some interventions, such as improving organizational strategies and providing technical solutions, incentives and occupational facilities, can help reduce or eliminate these problems.